Cotton's Inferno : a Sheriff Cotton Burke western - Dunlap, Phil (Berkley Books, 2014)
When Carp Varner, a newcomer to Apache Springs, offers his services as a gunsmith, Sheriff Cotton Burke takes him up on his offer until he discovers Varner's true nature and past crimes.